Caracterización de la diversidad de resistencia antimicrobiana en los procesos de biodigestión para la reducción de escherichia coli blee de los residuos lecheros en la hacienda Lyg Farm en Quito – Ecuador. - Mancheno Saavedra, Rossana Carolina (2022)
Dairy cattle production in our country does not have correct waste management since they end up in storage pits, in water sources, and used for agricultural purposes. The problem of poor waste management lies in environmental contamination and the dissemination of pathogenic agents, such as E. coli, classified as multi-resistant. The excessive and inadequate use of antimicrobials, especially in livestock production, has caused this. Therefore, this research was carried out to use a biodigester to reduce the amount of E. coli BLEE present in the dairy waste. So, three sampling points were taken, at the beginning (SP1), during (SP2), and after (SP3) the digestion process, and the total E. coli and E. coli BLEE counts were calculated. Coli BLEE counts were calculated by TBX filtration and TBX combined with 5 µl/ml cefotaxime, while susceptibility to 21 antimicrobials belonging to 10 families was evaluated by the Kirby-Bauer method and blaCTX-M genes groups 1, 2, 8 and 9 were analyzed by multiplex PCR. SP1 quantified 2833.3 CFU/ml of E. coli BLEE, while SP3 presented 0.75 CFU/ml. Its reduction could be due to mesophilic temperature and syntrophy due to the microorganisms present in the biodigester. Sixteen samples of E. coli BLEE were isolated for analysis, where it showed multi-resistance to 15 of the 21 antimicrobials used; SP1 reported resistance to 7, while SP3 reported 14. The increase was indicated by the evolutionary characteristics of E. coli and other factors that affect the digestion process. Then, in the blaCTX-M gene analysis, groups 2 and 8 obtained the highest prevalence, including the digestion process reduced by 75% the presence of E. coli with the blaCTX-M-2 gene from SP1 to SP3. The research determined that the presence of E. coli BLEE was reduced, which would allow obtaining fertilizers with less presence of pathogens being a benefit for public health. However, it is not the case of antimicrobial resistance since the genetic mechanisms of E. coli did not reduce this, so other methods that allow for reducing multi-resistance would have to be determined.